2009
DOI: 10.1007/s10517-009-0672-2
|View full text |Cite
|
Sign up to set email alerts
|

Neurotransmitter Mechanisms of Morphine Withdrawal Syndrome

Abstract: Activity of the major neurotransmitter systems in the brainstem and cerebellum was studied in rats with morphine withdrawal syndrome. The most significant changes were found in the brainstem of animals by the 36th hour and 7 days after morphine withdrawal. Dysfunction was revealed in the dopaminergic, noradrenergic, and serotoninergic neurotransmitter systems. Changes in cerebellar neurotransmission were most pronounced by the end of the first week of morphine withdrawal syndrome and manifested in the prevalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…4 There are multiple neurotransmitter systems, such as dopaminergic, GABAergic, cholinergic, glutamatergic, serotonergic, orexinergic and noradrenergic systems that play an important role in the development of opioid dependency and withdrawal signs. [5][6][7][8][9][10][11][12][13][14][15][16] There is a close relationship between major neurotransmitter systems in the brain, thus any changes in one of these systems can alter other systems. 7 Medicinal plants have attracted a wide range of attention in the treatment of drug dependency, because of their fewer side effects and costs than synthetic drugs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 There are multiple neurotransmitter systems, such as dopaminergic, GABAergic, cholinergic, glutamatergic, serotonergic, orexinergic and noradrenergic systems that play an important role in the development of opioid dependency and withdrawal signs. [5][6][7][8][9][10][11][12][13][14][15][16] There is a close relationship between major neurotransmitter systems in the brain, thus any changes in one of these systems can alter other systems. 7 Medicinal plants have attracted a wide range of attention in the treatment of drug dependency, because of their fewer side effects and costs than synthetic drugs.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13][14][15][16] There is a close relationship between major neurotransmitter systems in the brain, thus any changes in one of these systems can alter other systems. 7 Medicinal plants have attracted a wide range of attention in the treatment of drug dependency, because of their fewer side effects and costs than synthetic drugs. [17][18][19] One of the useful and wellknown medicinal plants is saffron (Crocus sativus L.).…”
Section: Introductionmentioning
confidence: 99%
“…The number of jumping is one of the most important signs to determination the severity of morphine withdrawal signs (2). Previous studies have reported that serotonergic, cholinergic, and GABAergic systems are involved in the number of jumping caused by morphine withdrawal syndrome (3)(4)(5)(6)(7)(8). In this regard, it has been shown that the serotonergic and cholinergic systems increase the number of jumping and the GABAergic system reduces the number of jumping in morphine dependent mice (26).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that various systems, including dopaminergic, noradrenergic, and GABAergic systems are involved in the process of development of these signs. However, studies on the impact of other effective systems on the development of morphine withdrawal signs are still ongoing (3)(4)(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, many researchers investigated the mechanisms of the withdrawal syndrome to fi nd an eff ective medical treatment that might improve the ability of addicts to discontinue the opiate intake with less side eff ects and better quality of effi cacy. Hence, alteration in noradrenergic [ 32 ] , serotonergic [ 33 ] , dopaminergic [ 34 ] , purinergic [ 35 ] , glutamatergic [ 36 ] , and neurotransmitter systems are reported as possible involvement mechanisms in the morphine withdrawal syndrome. Furthermore, Robert's study suggested that the biogenic amine systems are involved in behavioral and physiological eff ects of the opiates [ 37 ] .…”
Section: Figmentioning
confidence: 99%